Repeated sprint cycling performance is not enhanced by ischaemic preconditioning or muscle heating strategies - Cocking, S.; Ihsan, M.; Jones, H.; Hansen, C.; Cable, N. T.; Thijssen, D. H. J.; Wilson, M. G. (European Journal of Sport Science, 2021)
Introduction: Both ischaemic preconditioning (IPC) and muscle heat maintenance can be effective in enhancing repeated-sprint performance (RSA) when applied individually, acting mechanisms of these interventions, however, likely differ. It is unclear if, when combined, these interventions could further improve RSA. Methods: Eleven trained cyclists undertook experimental test sessions, whereby IPC (4 × 5-min at 220 mmHg) and SHAM (4 × 5-min at 20 mmHg) were each performed on two separate visits, each combined with either passive muscle heating or thermoneutral insulation prior to an "all-out" repeated-sprint task (10 × 6-s sprints with 24-s recovery). Primary outcome measures were peak and average power output (W), whist secondary measures were muscular activation and muscular oxygenation, measured via Electromyography (EMG) and Near-infrared spectroscopy (NIRS), respectively. Results: IPC did not enhance peak [6 (-14-26)W; P = 0.62] or average [12 (-7-31)W; P = 0.28] power output versus SHAM. Additionally, no performance benefits were observed when increasing muscle temperature in combination with IPC [5 (-14-19) watts; P = 0.67], or in isolation to IPC [9 (-9-28)W; P = 0.4] versus SHAM. No changes in EMG or microvascular changes were present (P > 0.05, respectively) between conditions. Conclusion: Overall, neither IPC, muscle heating, or a combination of both enhances RSA cycling performance in trained individuals.